Revision of Liparis (Orchidaceae, Epidendroideae, Malaxidinae) in Brazil - dos Santos, Thiago Faria [UNESP]; Coan, Alessandra Ike [UNESP]; de Camargo Smidt, Eric [UNESP] (FapUNIFESP (SciELO), 2023)
The presence of Liparis occurring in Brazil was revised, resulting in three taxons confirmed in national territory. Nine lectotypifications and six neotypifications, together with L. inundata being demoted to a synonym of L. nervosa, are proposed. Species can be distinguished by the leaf blade, the number of leaves per pseudobulb and the presence of calluses in the lip. From those, only L. cogniauxiana is endemic to the country, being restricted to the Cerrado biome. Liparis nervosa occurs in all Brazilian biomes and is the only one registered in the Pampas and the Caatinga, while L. vexillifera occurs in the Atlantic Forest, Amazon and Cerrado biomes. According to the IUCN criteria, L. cogniauxiana, L. nervosa and L. vexillifera are in the ‘‘Least Concern (LC)’’ category due to a broad distribution, the number of occurrences, presence in protected areas and low pressure from indiscriminate collecting.
Keywords: nomenclature; South America; systematics; taxonomy